Scalar dark matter search from the extended νTHDM - Seungwon Baek (Journal of High Energy Physics, 2018)
Abstract We consider a neutrino Two Higgs Doublet Model (νTHDM) in which neutrinos obtain naturally small Dirac masses from the soft symmetry breaking of a global U(1) X symmetry. We extended the model so the soft term is generated by the spontaneous breaking of U(1) X by a new scalar field. The symmetry breaking pattern can also stabilize a scalar dark matter candidate. After constructing the model, we study the phenomenology of the dark matter: relic density, direct and indirect detection.